An immunoproteomics study of antisera from patients with gonorrhea identifies novel Neisseria gonorrhoeae proteins - Dijokaite-Guraliuc, Aiste; Humbert, Maria Victoria; Skipp, Paul; Cleary, David W.; Heckels, John E.; Christodoulides, Myron (Frontiers in Bacteriology, 2023)
Background: Neisseria gonorrhoeae (gonococcus) is the causative agent of the sexually transmitted disease gonorrhoea, for which no vaccines exist. Efforts are being made to identify potential vaccine protein antigens and, in this study, an immunoproteomics approach was used to identify protein signatures in gonococci that were recognised by sera from patients with gonorrhoea. Methods: sera from patients with uncomplicated gonorrhoea and from controls were reacted on western blot with gonococcal whole cell lysate separated by 2D electrophoresis. Reactive bands were excised and digested, and peptides analysed by mass spectrometry to identify protein hits. Proteins were analysed with in silico bioinformatics tools (PSORTb v3.0, CELLO, SOSUI-GramN, LipoP 1.0, SignalP 5.0, TMHMM 2.0, eggNOG-mapper 5.0) to select for surface-exposed/outer membrane proteins (OMP) and exclude cytoplasmic proteins and most periplasmic proteins. Sera were tested for bactericidal activity against homologous and heterologous gonococcal strains. Results: patient sera reacted with 180 proteome bands, and 18 of these bands showed ≥ 2-fold increased reactivity compared to sera from individuals (n=5) with no history of gonococcal infection. Mass spectrometry produced peptide signatures for 1107 proteins and after bioinformatics analyses, a final collection of 33 proteins was produced that contained 24 OMP/extracellular proteins never previously studied to our knowledge, 6 proteins with homologues in N. meningitidis that can generate functional immune responses and 3 unknown proteins. The sera showed little or no significant bactericidal activity, which may be related to the immunoproteomic identification of contra-indicated proteins Rmp and H.8 that can generate blocking antibodies. Conclusions: Studies on the vaccine potential of these newly identified proteins deserve consideration.